Increasing Incidence and Imaging in Pediatric Head and Neck Cancer and Role of the Human Papilloma Virus and Epstein–Barr Virus - Kirsch, Claudia F. E.; Dellacerra, Gary (Journal of Pediatric Neuroradiology, 2016)
Over the past few decades, the incidence of head and neck squamous cell carcinomas in the pediatric population and tumors associated with oncogenic human papilloma virus (HPV) has continued to increase. Previously, head and neck cancers in young patients were considered rare and—only in patients with genetic risk factors, with clinicians unaware of these neoplasms—occurring with greater frequency in younger patients, and often associated with HPV infection. This article reviews the viral oncogenic properties of HPV and Epstein–Barr virus, what the biomarker p16 represents, and the salient clinical and radiographic features of these tumors. Clinical awareness of these features is important to identify these tumors and initiate appropriate therapeutic treatment and to avoid any delay in diagnosis.
Keywords: human papilloma virus; Epstein–Barr virus; head and neck cancer; pediatric patients